The Role of Collectors in the Establishment of Museums (In the Case of Tashkent City) - Nazarova, Dilnoza (International Journal on Integrated Education, 2023)
This article explores the role of collectors in the establishment of museums in Central Asia, under the patronage of the Russian Empire. Specifically, it provides information about archaeologist scholars who have been overlooked in the history of Uzbek archaeology during the latter half of the 20th century.